2021
DOI: 10.1093/function/zqab024
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Adam10 Disrupts Ion Transport in Immortalized Kidney Collecting Duct Cells

Abstract: The kidney cortical collecting duct (CCD) comprises principal cells (PCs), intercalated cells (IC), and the recently discovered intermediate cell type. Kidney pathology in a mouse model of the syndrome of apparent aldosterone excess revealed plasticity of the CCD, with altered PC:intermediate cell:IC ratio. The self-immortalized mouse CCD cell line, mCCDcl1, shows functional characteristics of PCs, but displays a range of cell types, including intermediate cells, making it ideal to study plasticity. We knocked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The combination of these features makes mCCD cl1 cells a very attractive research model. Since then, numerous advancements in renal physiology have been published based on work done with mCCD cl1 cells, including the study by Assmus et al, 5 which was recently published in Function . In this study, the authors utilize mCCD cl1 cells to study collecting duct cell plasticity.…”
Section: A Perspective On “Loss Of Adam10 Disrupts Ion Transport In Immortalised Kidney Collecting Duct Cells”mentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of these features makes mCCD cl1 cells a very attractive research model. Since then, numerous advancements in renal physiology have been published based on work done with mCCD cl1 cells, including the study by Assmus et al, 5 which was recently published in Function . In this study, the authors utilize mCCD cl1 cells to study collecting duct cell plasticity.…”
Section: A Perspective On “Loss Of Adam10 Disrupts Ion Transport In Immortalised Kidney Collecting Duct Cells”mentioning
confidence: 99%
“…Using the CRISPR-Cas gene editing strategy to knockout Adam10 in mCCD cl1 cells, Assmus and colleagues 5 demonstrated that loss of Adam10 results in significantly reduced amiloride sodium transport. Going further, the authors performed single-cell RNA sequencing to compare the transcriptomes of the knockout line to the original mCCD cl1 line.…”
Section: A Perspective On “Loss Of Adam10 Disrupts Ion Transport In Immortalised Kidney Collecting Duct Cells”mentioning
confidence: 99%